Discrimination and Exploitation of Labour in Mulk Raj Anand’s Coolie - Adhikari, Bina (Cognition, 2023)
This paper discusses about a story of the sufferers in Indian society of Mulk Raj Anand’s novel coolie. It describes the class distinction between the wealthy and the needy person. The upper- class people abused to lower class people humiliated them for minor faults and sometimes without any reason. It also explains the significant condition, bitter and miserable life of Munoo, a young boy of the village Bilaspur. The novel portrays the Indian society where social interactions of accomplishment and scarcity determine the life of Munoo, key person of the story. He is like the hero of John Galsworthy, English novelist and is the universal figure who represents the discomfort and measurable life of the poor and down-trodden. There is a human tragedy in the novel caused by the scarcity, exploitation, hunger, selfishness and torture. His life as a labourer in Bombay at the British-owned White cotton mills are described in fourth chapter. Munoo is exhibited as a servant and rickshaw coolie in the employ to Mrs. Mainwaring house, in Simla. A most vivid panorama of life in India of that period can be felt during the period of job searching from his native hills to the cities. It is not the destiny who is responsible for the disaster of Munoo but it is the society in which he is brought-up. He is a victim of social interactions in his life. Coolie represents very sensitive issue in the society where child work is the worst kind of social abuse. Mulk Raj Anand focuses crisis of these innocents in a very sensitive way critically. This article focuses on discrimination and exploitation faced by labour.